ЖИНОЯТ-ИЖРОИЯ ҚОНУНЧИЛИГИНИ ТАКОМИЛЛАШТИРИШ МАСАЛАЛАРИ - Эргaшев А.Б (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
The scientific document analyzes the need to improve the legislation of the Republic of Uzbekistan on the criminal executive branch and examines such issues as, for example, shuningdek, legislation offering normal ethics.